The Authority of Bali Governor in Regulating The Control of Corona Virus Disease 19 - Wiryawan, I Wayan; Sumerta Yasa, Putu Gede Arya; R, Ibrahim (Kertha Patrika; Vol 43 No 3 (2021)DO - 10.24843/KP.2021.v43.i03.p03, 2021)
The Governor of Bali Province Regulation Number 46 of 2020 was formed on a delegation owned by the Governor of Bali. However, thus Governor Regulation includes fines and their application on the spot. The authority of the Governor Bali to include fines in the form of money is a polemic in the community and at the same time a legal problem because it is related to the legal norms set forth in the governor's regulation. The purpose of this research is to analyze the authority of the Governor of Bali in regulating the control of Corona Virus Disease 19 and to analyze the form of control of the Corona Virus Disease 19 in the Province of Bali. This research uses normative legal research. The results of this study indicate that the authority of the Governor Bali in regulating the control of Corona Virus Disease 19 only regulates the control of Corona Virus Disease 2019 in Bali. The authority to control Corona Virus Disease 2019 in Bali remains with the Central Government, while the Governor of Bali is only given assistance tasks. Controlling the Corona Virus Disease 2019 in Bali is a concurrent business of the Central Government. Therefore, the authority remains with the Central Government, not the Bali Provincial Government. The form of controlling the Corona Virus Disease 19 in the Province of Bali is carried out based on the principle of deconcentration. The implementation of the principle of deconcentration is carried out by delegating co-administration tasks to the Governor of Bali.